Creation and evolution of inflation expectations in Paraguay - Pablo Alonso (Inter-American Development Bank (IDB), 2018)
The establishment of the inflation targeting regime in Paraguay is relatively recent, however, the results have been satisfactory. This is because based on the observed data, from the implementation of this framework, it has been possible to not only reduce inflation levels, but also align inflation expectations along the medium-term inflation target. Previously the implementation, both of these variables were characterized by significant volatility. Therefore, it can be affirmed that the inflation targeting regime has provided relevant information to economic agents on the monetary policy objectives, which has helped guide their inflation expectations. This paper seeks to identify the main determinants of the formation of inflation expectations in Paraguay since the adoption of the inflation targeting regime. This work bases the analysis on the results obtained from the expectations surveys conducted by the country's monetary authority. Likewise, it is important to note that the dispersion of the respondents' answers was adjusted within the inflation range and that it has also decreased according to the reduction in this range. This further evidences the effectiveness of the expectations channel, thanks to the credibility that the central bank has been achieving.
Keywords: E31; E52; E58; 330; Inflation targeting; Inflation expectations; Monetary policy